THE EFFECT OF FINANCIAL LITERACY AND RISK ATTITUDE ON INVESTOR BEHAVIOR - Livia Della Ramandhanty; Alfiyatul Qomariyah S.Ak., M.BA., Ph.D.,; Fatih Andesita Wuri Bemby (Universitas Airlangga, 2021)
This research aims to examine the related effects of financial literacy and risk attitudes towards investor behavior in the Indonesian capital market with the motive of saving as a mediating variable. This study uses a quantitative approach and partial least squares- structural equation modelling (PLS-SEM) to test hypotheses. The research data was obtained from 110 questionnaires distributed to capital market investors in Indonesia using the purposive sampling method. The results of this study indicate that financial literacy, risk attitude and saving motives have positive and significant effects on investor behavior in the Indonesian capital market. The influence of financial literacy and risk attitude also has a positive and significant effect on saving motives. However, the motive for saving money cannot mediate the effect of financial literacy and risk attitude on investor behavior. Theoretically, the implications of the results of this study are the level of financial literacy, risk attitude, and saving motives can directly influence investor behavior. The higher the financial literacy, the better the attitude in facing investment risk and the greater the motive for saving, the better the investor's behavior in making investment decisions. Whereas in practical terms, this implication is used as input for investors to further increase financial literacy, pay attention to the level of risk of selected investments, and enlarge the motives for saving so that the purpose of investing can be achieved well.